2020
DOI: 10.1111/jbi.13922
|View full text |Cite
|
Sign up to set email alerts
|

Did long‐term fire control the coniferous boreal forest composition of the northern Ural region (Komi Republic, Russia)?

Abstract: Aim: Documenting past vegetation dynamics and fire-vegetation relationships at a regional scale is necessary to understand the mechanisms that control the functioning of the boreal forest, which is particularly sensitive to climate change. The objective of this study is to document these interactions in the Komi Republic during the Holocene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 84 publications
(158 reference statements)
2
15
1
Order By: Relevance
“…Although some studies draw a similar conclusion (e.g. Carcaillet et al, 2001 in eastern Canada), this result contrasts with many other studies from the Eurasian and North American boreal zones, where vegetation changes were found to be closely connected to changes in fire regimes (Barhoumi et al, 2019(Barhoumi et al, , 2020Feurdean et al, 2020;Gavin et al, 2007;Kelly et al, 2013). However, on a shorter, multidecadal timescale, phases with more Cyperaceae pollen (sedges) in the Lake Khamra record and a higher ratio of evergreen to deciduous arboreal pollen types coincide with periods of high fire activity in phases 2 and 4 (see Fig.…”
Section: Vegetationcontrasting
confidence: 93%
“…Although some studies draw a similar conclusion (e.g. Carcaillet et al, 2001 in eastern Canada), this result contrasts with many other studies from the Eurasian and North American boreal zones, where vegetation changes were found to be closely connected to changes in fire regimes (Barhoumi et al, 2019(Barhoumi et al, , 2020Feurdean et al, 2020;Gavin et al, 2007;Kelly et al, 2013). However, on a shorter, multidecadal timescale, phases with more Cyperaceae pollen (sedges) in the Lake Khamra record and a higher ratio of evergreen to deciduous arboreal pollen types coincide with periods of high fire activity in phases 2 and 4 (see Fig.…”
Section: Vegetationcontrasting
confidence: 93%
“…5). The reconstructed fire return interval (FRI) in the study area is largely in line with other sites located in forested peatlands (Pinus-Betula-dominated, Picea obovata, Abies sibirica) in Russia, which report an FRI range between 100 and 600 years (Barhoumi et al, 2019(Barhoumi et al, , 2020(Barhoumi et al, , 2021. In contrast to a study in the northern Ural region (Barhoumi et al, 2019), we have not found a gradual increase in fire frequency from the early Holocene towards the present, but rather two distinct periods of enhanced activity between 7.5 and 4 ka and approximately over the last 2 kyr (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…5). The reconstructed fire return interval (FRI) in the study area is in line with those from other sites located in forested peatlands (Pinus-Betula dominated, Picea obovata, Abies sibirica) in Russia, which report an FRI range between 100 and 600 yr (Barhoumi et al, 2019(Barhoumi et al, , 2020. In contrast to these studies, we have not found a gradual increase in fire frequency from the early Holocene towards the present, but rather two distinct periods of enhanced activity, between 7.5 and 4 ka, and approximately over the last 2 ka (Fig.…”
Section: Changes In Fuel Fire Type and Fire Frequency Over The Holocenesupporting
confidence: 82%